The Effectiveness of the Two Stay Two Stray (TSTS) Cooperative Learning Model on Students' Interest in Islamic Religious and Character Education - Selawati; Ahmad Fatoni; Waluyo Erry Wahyudi (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2025)
Student learning interest is one of the key factors in the success of the learning process, especially in Islamic Religious Education (PAI) subjects that emphasize the formation of values ​​and character. Initial observations at SMP Negeri 1 Bandar Lampung showed low student involvement and interest in PAI learning due to the dominant use of conventional methods that are less interactive. This study aims to analyze the effect of the Two Stay Two Stray (TSTS) cooperative learning model on student learning interest in PAI subjects. The study used a quantitative approach with a quasi-experimental method through a post-test only control group design. The sample consisted of two classes, namely VII.9 as the experimental class that received the TSTS model treatment and VII.4 as the control class. Data were collected using a non-test questionnaire that measures two indicators of learning interest: involvement and interest. Data analysis included normality tests, homogeneity tests, and hypothesis testing using t-tests. The results showed a significant effect of the TSTS model on student learning interest with a significance value of 0.001 (p <0.05). These findings confirm that the TSTS model is effective in creating a collaborative learning environment, increasing student participation, and encouraging interaction and information exchange between groups. Therefore, the TSTS cooperative learning model is worthy of recommendation as an alternative strategy to increase learning interest in Islamic Religious Education (PAI).